MODEL SISTEM KELEMBAGAAN PENGEMBANGAN INDUSTRI TALAS - Iffan Maflahah (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
Taro is one of alternative stapple food. For fullfiling stapple food, it is needed supply of raw material. Institution aspect will show the structure of object interchanged as a free flow. The goals of this research are to formulate model of structural system of taro industry development and strategy of taro industry development. The formulation of model uses ISM (Intrepretative Structural Modelling). This model uses some elements are to build a stronginstitution, government support, merchant, the rise of product diversification of taro, the weakness of institution system, the less of government support in taro industry development and the less of training through farmer, and to form an independent farmer group in taro plantation.